Employee Assessment Through Performance - Hatoguan Pasaribu, Fridholin; Farida Ferine, Kiki (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
This research aims to examine the influence of competency, integrity and organizational culture on employee performance with job satisfaction as an intervening variable. The phenomenon that occurs at BPJS Employment in the range and in Palu is that there is still a lack of employee competency so that employee performance is not optimal. There are employees who are competent but there are not many. This is because the organizational culture is bad and uncontrolled so that employee integrity is also compromised. In this incident, many employees feeling dissatisfied with the organization's attention to its employees is the reason why employees do not express their abilities to the organization because the organization does not treat employees well to the point that employees limit themselves to working at BPJS Employment in the range and city of Palu. The results of this research are as follows: Organizational Culture has a positive and significant effect on Job Satisfaction with an original sample value of 0.397 and a p value of 0.000. Organizational culture has a positive and significant effect on employee performance with an original sample value of 0.233 and a p value of 0.002. Integrity has a positive and significant effect on Job Satisfaction with an original sample value of 0.357 and a p value of 0.000. Integrity has a positive and insignificant effect on employee performance with an original sample value of 0.069 and a p value of 0.171. Job satisfaction has a positive and significant effect on employee performance with a value of 0.644 and a p value of 0.000. Competency has a positive and significant effect on Job Satisfaction with an original sample value of 0.194 and a p value of 0.009. Competence has a positive and insignificant effect on employee performance with an original sample value of 0.023 and a p value of 0.383. Organizational Culture has a positive and significant indirect effect on Employee Performance through Job Satisfaction with an original sample value of 0.256 and a p value of 0.000. Integrity has a positive and significant indirect effect on employee performance through job satisfaction with an original sample value of 0.230 and a p value of 0.000. Competency has a positive and significant indirect effect on employee performance through job satisfaction with an original sample value of 0.125 and a p value of 0.020.